Komparasi Efisiensi Kinerja Bank Umum Syariah Di Indonesia Tahun 2023 - Mukti, Titania (el-Amwal, 2024)
Sharia banking has an important role for economic progress and national development, but the problem faced is the development of the sharia banking industry itself which is growing slowly compared to conventional banks. One of the benchmarks for knowing the development of sharia commercial banks in Indonesia is the performance efficiency of each sharia commercial bank. This research aims to compare the performance efficiency of sharia commercial banks in Indonesia in 2023. The research method used is quantitative analysis using Data Envelopment Analysis (DEA). The sample used is a saturated sample, which means taking all the existing population as a sample. The sample for this research is 13 financial reports of Islamic commercial banks in Indonesia in 2023. The results of the research show that measuring efficiency using Data Envelopment Analysis (DEA) with a Constant Return To Scale (CRS) approach and input orientation, the results obtained are that PT Bank Aladin Syariah Tbk, PT Bank KB Bukopin Syariah, PT Bank Panin Dubai Syariah Tbk, and PT Bank Tabungan Pensiun Negara Syariah Tbk have an efficiency value of 100% so these four banks are said to be efficient.